Usability and Feasibility Study of a Remote Cognitive Behavioral Therapy System with Long-Term Unemployed Women. Issue 3 (3rd July 2017) - García, Yolanda; Ferrás, Carlos; Aguilera, Adrián; Ávila, Patricia
ABSTRACT: We present the results of the use of a cognitive behavioral therapeutic intervention tool to improve the mental, physical, and social health of a group of long-term unemployed women in Spain. Method: We sent automated text messages (SMS) to the mobile phones of long-term unemployed women selected at random from public social services. During a 28-day intervention period, women received four daily automated text messages on her mobile phone on a predetermined hourly schedule. We measured depression symptoms at the start and end of the intervention and we analyzed qualitative data to determine the acceptability of a remote SMS program. Results: Depression symptoms using the Personal Health Questionnaire-9 (PHQ-9), went from an average of 13.8 at baseline to 4.9 at the end of 28 days ( p  = 0.89). One hundred percent of the women reported that they liked receiving the text messages and most found them helpful.